Recursos educativos digitales abiertos del Ministerio de Educación del Ecuador para el nivel de básica media utilizados por los docentes de las escuelas de educación general básica y unidades educativas fiscales de la ciudad de Loja en el año lectivo 2022-2023 - Sarango Condoy, Angy Yadira (2023)
Currently, the educational process in Ecuador, within its guidelines, promotes innovation through the use of technology; the Ministry of Education of Ecuador is developing various alternatives for teachers to strengthen the teaching-learning process in an integral and holistic manner. In this sense, this curricula Integration Work intends to contribute with research focused on defining the use of Open Digital Educational Resources (REDA) of the Ministry of Education of Ecuador for the middle school level by teachers of general basic education schools and public educational institutions in the school year 2022-2023. In order to develop this research, the following methodology is used, deductive method, quantitative approach, and exploratory-descriptive type. It should be emphasized that the target group considered consisted of 22 teachers from various institutions and educational schools of government assistance in the city of Loja. In this research work, an ad hoc questionnaire was developed based on the Ministry of Education portal of open digital educational resources, which was applied through the survey technique, and the results allowed to identify and to describe the open digital educational resources for the middle school level through a descriptive table of the 24 resources that were required to proceed with the diagnosis of the use of open digital educational resources in the areas of Social Sciences, Natural Sciences, Artistic Cultural Education and Physical Education. Finally, a continuous training course is recommended to strengthen the use of the portal resources. Key words: Innovation, Technology, REDA,